THE IMPORTANCE OF INDEPENDENT LEARNING IN THE MODERN EDUCATIONAL PROCESS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, the author examines the importance of independent education in the professional training of future teachers of musical culture, the skills of self-control of a student’s musical ear during independent learning, and the principles of organizing independent work.